2010
DOI: 10.1016/j.jada.2009.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Food Selectivity and Sensory Sensitivity in Children with Autism Spectrum Disorders

Abstract: Autism spectrum disorders (ASDs) comprise a complex set of related developmental disorders that are characterized by impairments in communication, social interaction, and repetitive behaviors. Impairments in sensory processing are also extremely common. The prevalence of ASDs is increasing and is currently estimated to affect 1 in 150 children. ASDs are considered to be a major health and educational problem, affecting many areas of daily living, including eating. Children with ASDs are often described as pick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
311
3
17

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 535 publications
(349 citation statements)
references
References 36 publications
18
311
3
17
Order By: Relevance
“…In line with the study of Bandini et al (2010), we did not observe the high frequency consumption of a single food in our sample: only 9 parents of the FS group reported that their child consumed a single food more than 4-5 times daily. Studies have hypothesized sensory sensitivity as a possible mechanism underlying food selectivity (Cermack et al, 2010;Mazurek et al, 2013;Suarez et al, 2013). A recent longitudinal follow-up study examining the relationship between food selectivity and sensory over-responsivity in 52 children with ASD, at baseline and after 20 months, reported that higher level of overresponsivity were associated with fewer foods accepted and this association appeared to be stable over time (Suarez et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the study of Bandini et al (2010), we did not observe the high frequency consumption of a single food in our sample: only 9 parents of the FS group reported that their child consumed a single food more than 4-5 times daily. Studies have hypothesized sensory sensitivity as a possible mechanism underlying food selectivity (Cermack et al, 2010;Mazurek et al, 2013;Suarez et al, 2013). A recent longitudinal follow-up study examining the relationship between food selectivity and sensory over-responsivity in 52 children with ASD, at baseline and after 20 months, reported that higher level of overresponsivity were associated with fewer foods accepted and this association appeared to be stable over time (Suarez et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have observed that gastrointestinal (GI) problems are common in ASD and, even though the results are contrasting, food selectivity may contribute to GI problems in a portion of these individuals (Chaidez, Hansen, & Hertz-Picciotto, 2014;Gorrindo et al, 2012;Horvath & Perman, 2002;Ibrahim, Voigt, Katusic, Weaver, & Barbaresi, 2009;Maenner et al, 2012;Mazefsky, Schreiber, Olino, & Minshew, 2014;Mazurek et al, 2013;Mouridsen, Isager, & Rich, 2013;Nikolov et al, 2009;Valicenti-McDermott, McVicar, Cohen, Wershil, & Shinnar, 2008;Whitehouse, Maybery, Wray, & Hickey, 2001). Furthermore, it has been suggested that sensory processing problems, such as sensory sensitivity, which are common among individuals with ASD, could be possible mechanisms underlying food selectivity (Cermack, Curtin, & Bandini, 2010;Mazurek et al, 2013;Suarez et al, 2013). In fact, determining factors of food selectivity are often associated with texture, taste, temperature, smell preferences and consistency (Williams et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Hazen et al 22 and Cermak et al 4 estimated the prevalence of sensory processing disorders to range from 69 to 95% in children of various ages with ASD. In this study, however, the dietary profile of the children reflected the families' preferences.…”
Section: Food-related Behaviormentioning
confidence: 99%
“…3 Furthermore, sensory factors such as smell, texture, color and temperature may contribute to this behavior. [4][5][6] A literature review of seven descriptive studies found the prevalence of eating problems in children with ASD to range between 46 and 89% in the patients evaluated. 7 The most common problems found in those studies were: limited food intake; refusal to eat certain foods or selectivity related to the texture, smell and taste of food; inflexibility regarding the use of utensils, brands and packaging; and behavioral and nutritional problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation